Systematic exploration of psychiatric genetic research publications in Latin America - Garro Núñez, Diana (2022)
Background: Psychiatric and neurological disorders represent approximately 22% of the total diseases that affect populations in Latin America and the Caribbean. Even though psychiatric disorders have a great impact in terms of mortality, morbidity, and disability across all stages of life, research in mental health has not been a focus for funding agencies, in comparison to other health related research areas. In spite of this situation, several research efforts in different Latin American countries have focused on the genetics of psychiatric disorders. Additionally, some large international research initiatives have included populations of Latin American origin. The aim of this study is to review the research published with Latin American populations between 2010-2019. We focused mainly on sources of funding, and how this is related to the scope and complexity of the study. Methods: We performed a systematic literature search from 2010-2019 in the RedalyC and PubMed databases in Spanish, Portuguese, and English. The search terms were constructed with the following format: “Genetic” AND “Psychiatric disorder”, with the phrase “psychiatric disorder” being sequentially replaced by each of ten of the most common psychiatric disorders. Results: In general, more articles were published within the 2015-2016 period. Additionally, between the 2010-2019 period, depression (20%) and Alzheimer (19%) were the most common disorders found. Most of the Latin American countries' publications were internationally funded, with the exception of Brazil, for which 86% of all publications were locally funded. We found differences between locus specific studies and genome wide studies, regarding sources of funding (local or international) (x^2=9.46; p=0.009). 82% of all whole genome studies were funded by international sources. Over 70% of the studies used SNPs, mostly for association studies, and studies with endophenotypes or traits associated with the disorder. Finally, case/control studies represented the most frequent study design (42%), however an important proportion of the studies were family-based (33%). Discussion: Our results showed that local funds are generally not large enough for genome-wide studies in Latin America, with the exception of Brazil. As a result, larger studies are often done in collaboration with international partners. We also found that in larger studies the participants are Latin American ancestry subjects living in the USA, not in Latin America. Additionally, our results showed the important role of family-based studies, which have traditionally been a strength in Latin American genetic research because of large family sizes. In conclusion, limited local funding for research in Latin America has probably contributed to limited sample size, scope, and complexity of psychiatric genetic research studies. Increasing diversity in psychiatric genetics needs to be a future goal in order to improve generalizability and applicability in clinical settings.